A multi-innovation generalized extended stochastic gradient algorithm for output nonlinear autoregressive moving average systems - Hu, Yuanbiao; Liu, Baolin; Zhou, Qin (Applied mathematics and computation, 2014)
This paper proposes a generalized extended stochastic gradient (GESG) algorithm for estimating the parameters of a class of Wiener nonlinear autoregressive moving average systems using the gradient search. In order to improve the convergence rates of the GESG algorithm, a multi-innovation GESG algorithm is derived. The simulation results indicate that the proposed algorithms can effectively estimate the parameters of a class of output nonlinear systems.